2009
DOI: 10.1213/ane.0b013e3181a1a5ed
|View full text |Cite
|
Sign up to set email alerts
|

The Shivering Threshold in Rabbits with JM-1232(−), a New Benzodiazepine Receptor Agonist

Abstract: A low dose of JM-1232(-) reduced the shivering threshold in rabbits approximately 0.8 degrees C which is similar to the effects in humans given premedication doses of midazolam. In contrast, a 10-fold larger dose reduced the threshold more than 2.5 degrees C. This is a substantial decrement and might facilitate induction of therapeutic hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…CMR is associated with a proportional change in CBF. Our preliminary experiment and our previous study [ 11 ] showed that JM-1232(-) decreases BIS values. BIS is commonly used to measure hypnotic effect, and appears reliable in rabbits [ 12 ].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…CMR is associated with a proportional change in CBF. Our preliminary experiment and our previous study [ 11 ] showed that JM-1232(-) decreases BIS values. BIS is commonly used to measure hypnotic effect, and appears reliable in rabbits [ 12 ].…”
Section: Discussionsupporting
confidence: 49%
“…JM-1232(-) has sedative and anesthetic properties, however, sedative and anesthetic doses of JM-1232(-) for rabbits have not been well documented. Masamune et al [ 11 ] reported that intravenous administration of JM-1232(-) at 0.01 mg/kg/min and 0.1 mg/kg/min combined with 0.2 minimum alveolar concentration of isoflurane reduced bispectral index (BIS) values in rabbits. However, BIS level at 0.01 mg/kg/min infusion and at 0.1 mg/kg/min infusion did not differ significantly [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One rabbit in the control group was excluded because of severe hyperglycemia, to approximately 300 mg dL − 1 . Two rabbits in the severe hypoglycemic group did not shiver at the time when the core temperature reached to 34 °C, accordingly they were treated as if they had shivered at 34 °C as in our previous study [18]. Characteristic data prior to cooling for each group are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Animals were prepared as our previous studies [17, 18]. Briefly, we anaesthetized a rabbit by inhalation of 4% isoflurane and 67% nitrous oxide with oxygen.…”
Section: Methodsmentioning
confidence: 99%